Mobile technology integration in the 2020s: The impact of technology leadership in the Malaysian context - Omar, Mohd Norakmar; Ismail, Siti Noor (Horizon Research Publishing, 2020)
Mobile technology is a growing technology in the education system around the world. Today's educational resources are easily accessible by using mobile technology at anytime and anywhere. As mobile technology is so essential, principals should play a vital role in stimulating teachers' efforts to use these devices as teaching aids in the classroom. Therefore, the purpose of this study is to identify the level of technology leadership, mobile technology integration and the relationship between the two variables. In addition, the study examines the influence of principals' technology leadership dimensions such as visionary leadership, digital age learning culture, excellence in professional practice, systemic improvement, and digital citizenship as predictors of teachers' mobile technology integration in teaching. A total of 376 secondary school teachers in the state of Kedah, Northern of Malaysia were selected as respondents through a quantitative approach involving systematic random sampling. This study also uses two instruments, namely the Principals Technology Leadership Assessment (PTLA) based on the NETS-A and UTAUT2. The results of the data analysis revealed that there is a strong positive relationship between principals' technology leadership and teachers' mobile technology integration in teaching process. Meanwhile, the findings also predicted that visionary leadership, systemic improvement and digital citizenship were the most significant contributors in influencing teachers to integrate mobile technology at secondary schools.